Efficiently Coupling the I-DLV Grounder with ASP Solvers. Issue 2 (4th March 2020) - CALIMERI, FRANCESCO; DODARO, CARMINE; FUSCÀ, DAVIDE; PERRI, SIMONA; ZANGARI, JESSICA
Abstract : We present I-dlv+MS, a new answer set programming (ASP) system that integrates an efficient grounder, namely I-dlv, with an automatic selector that inductively chooses a solver: depending on some inherent features of the instantiation produced by I-dlv, machine learning techniques guide the selection of the most appropriate solver. The system participated in the latest (7 th ) ASP competition, winning the regular track, category SP (i.e., one processor allowed).